2018
DOI: 10.1681/asn.2017080929
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Solute-Aryl Hydrocarbon Receptor-Tissue Factor Axis Associates with Thrombosis after Vascular Injury in Humans

Abstract: Individuals with CKD are particularly predisposed to thrombosis after vascular injury. Using mouse models, we recently described indoxyl sulfate, a tryptophan metabolite retained in CKD and an activator of tissue factor (TF) through aryl hydrocarbon receptor (AHR) signaling, as an inducer of thrombosis across the CKD spectrum. However, the translation of findings from animal models to humans is often challenging. Here, we investigated the uremic solute-AHR-TF thrombosis axis in two human cohorts, using a targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 53 publications
2
108
0
1
Order By: Relevance
“…This meta-analysis included five studies with heterogeneity in dialysis modalities (peritoneal dialysis or hemodialysis) and in the follow-up of patients. IS levels were correlated with an increased risk of arteriovenous fistula thrombosis after angioplasty in two studies [47,48]. These observational studies were limited by potential confounders between IS plasma levels and nutritional intake.…”
Section: Indoxyl Sulfate a Uremic Endotheliotoxin: Clinical Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…This meta-analysis included five studies with heterogeneity in dialysis modalities (peritoneal dialysis or hemodialysis) and in the follow-up of patients. IS levels were correlated with an increased risk of arteriovenous fistula thrombosis after angioplasty in two studies [47,48]. These observational studies were limited by potential confounders between IS plasma levels and nutritional intake.…”
Section: Indoxyl Sulfate a Uremic Endotheliotoxin: Clinical Evidencementioning
confidence: 99%
“…Moreover, the number of endothelial progenitor cells is inversely correlated with IS plasma levels [54,55]. This mechanism could impair neovascularization [48][49][50][51]. The endotheliotoxicity of IS was demonstrated in living kidney donors with an eGFR greater than 60 mL/mn/1.73 m 2 and increased IS plasma levels.…”
Section: Indoxyl Sulfate a Uremic Endotheliotoxin: Clinical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, indolic solutes produced by tryptophan metabolism, such as IS, could increase tissue factor expression through aryl hydrocarbon receptor (AHR) signaling. The relevance of the uremic solute-AHR-thrombosis pathway on thrombosis was observed in human studies as well [29,30]. Using fibrin stain, we demonstrated that the luminal loss of AV fistula was in part secondary to thrombus formation in the vessel wall.…”
Section: Discussionmentioning
confidence: 55%